A Comparative Study of Mutual Fund Portfolio Performance in Indonesia - Aprillia, Dewinta; Wijaya, Chandra; Indriati, Fibria (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2018)
A Mutual fund is one of the instruments in the capital markets that have an important role for investors. Through mutual funds, investors can invest their capital to get the returns with the risks that fit into each investor criteria. Asset under Management (AUM) is one of the indicator for investors in choosing a mutual fund. The more capital is deposited by the investor into a mutual fund, the greater the managed fund. This study aims to analyze how the performance of the portfolio held by equity mutual funds with the largest of Asset under Management when the stock market condition tends to be bearish. This research was conducted through three measurements, a comparison of the performance of the mutual funds returns with a market return, mutual fund diversification using coefficient determination and mutual fund performance measurement using risk-adjusted return, which are Sharpe Ratio, Treynor Ratio and Jensen’s Alpha. The results showed that the use of the entire measurement, mutual funds performance with the largest AUM outperform the market, but different results obtained for diversification measurement and Jensen’s Alpha.